I now pronounce you Chuck and Larry [videorecording (DVD)] - Dugan, Dennis; Sandler, Adam; James, Kevin, 1965-; Biel, Jessica, 1982- (Universal Studios Home Entertainment, 2007)
Chuck and Larry are the pride of their fire station -- two guy's guys always side-by-side and willing to do anything for each other. Widower Larry wants just one thing, to protect his kids. His buddy Chuck also wants one thing, to enjoy the single life. Grateful Chuck owes Larry for saving his life in a fire, and Larry calls in his marker when civic red tape prevents him from naming his own two kids as his life insurance beneficiaries. All that Chuck has to do is claim to be Larry's domestic partner on some city forms. But when an overzealous bureaucrat becomes suspicious, the new couple's arrangement becomes a citywide issue and goes from confidential to front-page news. Chuck and Larry must now fumble through a charade of domestic bliss. After surviving their mandatory honeymoon and dodging the threat of exposure the well-intentioned con men discover that sticking together in your time of need is what truly makes a family.